Newspapers in classrooms: a pedagogical approach - Tomé, V.; Helena Menezes (REM - Ricerche su Educazione e Media, 2010)
This paper presents the results of the research project "Media Education in Castelo Branco - Portugal (2007-2010)" developed in 24 schools with 50 teachers and more than 600 students. The project focuses on the production of online and printed school newspapers with the help of pedagogical resources which were produced, validated and distributed to the schools by the research team. It also presents in-service on Media Education in the Castelo Branco region with 130 teachers from different subject areas and teaching levels.